Urgensi Adab sebagai Pondasi dalam Proses Belajar dan Pembelajaran - Nabila Rizqi Ramadhani; Ahna Hailu Sabilah; Siti Masyitoh (STIKes Ibnu Sina Ajibarang, 2025)
Etiquette is an essential aspect in the process of learning and education that is often overlooked in modern educational practices which tend to focus solely on cognitive achievements. In fact, in the tradition of classical scholarship, etiquette is the primary prerequisite in pursuing knowledge, even more important than mere mastery of the material. This article aims to deeply examine the urgency of etiquette as the fundamental foundation in the educational process, from both pedagogical perspectives and the spiritual values of Islam. This research uses literature study methods by examining various classical and contemporary educational literature. The results indicate that etiquette plays a crucial role in shaping attitudes of respect, discipline, and ethics in the interaction between teachers and students, as well as creating a conducive learning atmosphere that is full of blessings and character. Etiquette also proves to strengthen the intrinsic motivation of learners, and strengthen the positive emotional relationship between educators and learners. Therefore, the internalization of moral values must be a priority at every level of education, whether through the role modeling of teachers, integration into the curriculum, or habituation within the school environment. Education that only emphasizes intellectual aspects without moral values risks producing a generation that is academically intelligent but lacking in morals and ethics. Thus, moral values must be positioned as the main foundation in building a meaningful and sustainable learning process.